MiR‐290 Cluster Modulates Pluripotency by Repressing Canonical NF‐κB Signaling123. (22nd March 2012) - Lüningschrör, Patrick; Stöcker, Benedikt; Kaltschmidt, Barbara; Kaltschmidt, Christian
Abstract: Embryonic stem cell (ESC)‐specific microRNAs (miRNAs) play a critical role in the maintenance of pluripotency and self‐renewal but the complete network between these miRNAs and their broad range of target genes still remains elusive. Here we demonstrate that miR‐290 cluster, the most abundant miRNA family in ESCs, targets the NF‐κB subunit p65 (also known as RelA ) by repressing its translation. Forced expression of p65 causes loss of pluripotency, promotes differentiation of ESCs, and leads to an epithelial to mesenchymal transition. These data define p65 as a novel target gene of miR‐290 cluster and provide new insight into the function of ESC‐specific miRNAs. STEM CELLS 2012; 30:655–664